Accumulation, subcellular distribution, and oxidative stress of cadmium in Brassica chinensis supplied with selenite and selenate at different growth stages. (February 2019) - Yu, Yao; Fu, Pingnan; Huang, Qingqing; Zhang, Jingsuo; Li, Huafen
Abstract: Despite not being an essential element for plants, Se has been proved to reduce Cd accumulation and Cd-induced oxidative stress, although the underlying mechanisms are not fully understood. A pak choi hydroponic experiment was conducted to investigate the effects of Se on Cd accumulation, subcellular distribution, and Cd-induced oxidative stress at different growth stages. The results showed that on day 19 after germination, Cd content was significantly reduced by 32% by selenite, but was increased by 15% by selenate. Accordingly, selenite improved cell-wall Cd sequestration by 20%, whereas selenate caused enhanced translocation of Cd from the root to the shoot. However, the effects of selenite on the reduction in Cd accumulation and distribution in pak choi seedlings were completely dismissed on day 40. Nevertheless, both forms of Se enhanced antioxidative defense, as they both inhibited the accumulation of H2 O2 and malondialdehyde. On day 19, ascorbate peroxidase and glutathione reductase activities were increased by more than 50% by selenite; additionally, superoxide dismutase, catalase, and peroxidase activities increased by up to 86%, 63%, and 24%, respectively, in the presence of selenite, when compared to Cd treatment alone. Activities of most of the antioxidants remained significantly unaffected by both forms of Se on day 40. Consequently, selenite and selenate affected Cd accumulation in pak choi seedlings by altering Cd subcellular distribution and by enhancing antioxidative defense, but such effects depended on the Se forms applied and the growth stage as well. Highlights: Selenite reduced Cd content in shoots, while selenate increased it. Both Se treatments alleviated Cd-induced oxidative stress. Selenite improved Cd retention in the cell walls. Such effects was significant only on day 19.